Lower-thermospheric vertical wind measurements from the Arecibo radio observatory - Hysell, D. L.; Larsen, M. F. (Frontiers in Astronomy and Space Sciences, 2025)
Vertical wind profiles in the lower thermosphere computed from data from the Arecibo Radio Observatory between 2013 and 2016 are reviewed and analyzed. The estimates are derived from ion-line spectral measurements in the E and F regions made with the Arecibo dual-beam incoherent scatter radar using a number of specialized pulsing schemes. The background electric field is estimated on the basis of F-region samples, and its effects are then removed from E-region samples. Statistical inverse methods are used to estimate vector wind profiles in the lower thermosphere versus time. Data from the daytime E region and from nighttime sporadic- E layers are examined. We find large and highly variable vertical winds in the lower thermosphere at upper E-region altitudes. Frequency and vertical wavenumber spectra computed from the vertical wind estimates exhibit power laws, and the latter exhibit some degree of universality. The spectral forms are consistent with those measured in the mesosphere elsewhere. Theoretical interpretations of the spectral measurements are briefly reviewed.